Synergic Reaction Kinetics over Adjacent Ruthenium Sites for Superb Hydrogen Generation in Alkaline Media. Issue 20 (11th April 2022) - He, Qun; Zhou, Yuzhu; Shou, Hongwei; Wang, Xinyu; Zhang, Pengjun; Xu, Wenjie; Qiao, Sicong; Wu, Chuanqiang; Liu, Hengjie; Liu, Daobin; Chen, Shuangming; Long, Ran; et al.
Abstract: Ruthenium (Ru)‐based electrocatalysts as platinum (Pt) alternatives in catalyzing hydrogen evolution reaction (HER) are promising. However, achieving efficient reaction processes on Ru catalysts is still a challenge, especially in alkaline media. Here, the well‐dispersed Ru nanoparticles with adjacent Ru single atoms on carbon substrate (Ru1, n ‐NC) is demonstrated to be a superb electrocatalyst for alkaline HER. The obtained Ru1, n ‐NC exhibits ultralow overpotential (14.8 mV) and high turnover frequency (1.25 H2 s ‐1 at −0.025 V vs reversible hydrogen electrode), much better than the commercial 40 wt.% Pt/C. The analyses reveal that Ru nanoparticles and single sites can promote each other to deliver electrons to the carbon substrate. Eventually, the electronic regulations bring accelerated water dissociation and reduced energy barriers of hydroxide/hydrogen desorption on adjacent Ru sites, then an optimized reaction kinetics for Ru1, n ‐NC is obtained to achieve superb hydrogen generation in alkaline media. This work provides a new insight into the catalyst design in simultaneous optimizations of the elementary steps to obtain ideal HER performance in alkaline media. Abstract : Incorporating adjacent Ru nanoparticles and single atoms onto defective carbon as hydrogen evolution reaction electrocatalyst achieves ultralow overpotential and high intrinsic activity. The activity origin is the synergistic electronic regulations that facilitate water dissociation and reduce energy barriers of hydroxide/hydrogen desorption over adjacent Ru sites, resulting in an optimized reaction kinetics for alkaline hydrogen generation.